Valuasi Saham Dengan Pendekatan Price Earning Ratio Sebagai Dasar Pengambilan Keputusan Investasi - Moch Bahrul Anam; Nur Aini Anisa; Nur Farida (Populer: Jurnal Penelitian Mahasiswa, 2023)
The aim of this research is to determine appropriate investment decisions for infrastructure companies listed on the IDX in 2018–2022, based on intrinsic value calculations using the P/E Ratio (PER) approach. The research method used is quantitative descriptive, using the company's annual financial report data in calculating the company's intrinsic value. This study analyzes ten company stocks, including IPCM, LINK, NRCA, PBSA, POWR, TBIG, TLKM, TOTL, TOWR, and WEGE. The results of this research show that all shares of infrastructure companies selected as research objects are declared undervalued, so buying or increasing the ownership portion of these shares is the right investment decision.